2009
DOI: 10.1142/s0217984909018072
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Spark-Generated Bubble Interactions

Abstract: The complex interactions of two and three spark-generated bubbles are studied using high speed photography. The corresponding simulations are performed using a 3D Boundary Element Method (BEM) code. The bubbles generated are between 3 to 5 mm in radius, and they are either in-phase or out-of-phase with one another. The possible interaction phenomena between two identically sized bubbles are summarized. Depending on their relative distances and phase differences, they can coalesce, jet towards or away from one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…1d). Similar bubble dynamics have been observed in an unconstrained fluid medium using spark-generated vapor bubbles of millimeter size [15]. …”
Section: Bubble-bubble and Microjet-cell Interactionsupporting
confidence: 72%
“…1d). Similar bubble dynamics have been observed in an unconstrained fluid medium using spark-generated vapor bubbles of millimeter size [15]. …”
Section: Bubble-bubble and Microjet-cell Interactionsupporting
confidence: 72%
“…Experimental efforts have been made to study bubble interactions, using methods such as optical breakdown (laser) [43][44][45][46][47] , electric discharge [48][49][50] , small charge explosion 51 , and pressure impulse 52 . Bubble interaction has also been studied with numerical methods such as the boundary integral method coupled with fast multiple expansions [53][54][55][56] .…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies in the literature for interaction of three bubbles. Khoo et al 48 and Fong et al 49 carried out a few cases for three bubbles, where the bubble behavior was complicated, due to a number of factors such as bubble phases, sizes and positions. The current experiment is capable of generating three evenly distributed synchronized bubbles of the same size.…”
Section: Introductionmentioning
confidence: 99%
“…27 Studies of the motion of two cavitation bubbles generated directly beneath a free surface have shown that competition of the effects from the free surface and the bubbles' mutual interactions can result in a wide range of bubble behavior, including the jet formation. 28 Investigations of the interactions between a pair of bubbles have shown that the speed and direction of the liquid jet could be controlled by adjusting three dimensionless governing parameters of the bubble pair, [29][30][31][32][33] including the relative temporal difference of their initiation, τ, the relative size of the bubbles, ρ, and the relative initiation distance, γ. τ is defined as ∆t/T exp1 , where ∆t is the temporal difference of the bubble pair's initiation, and T exp1 is the expansion time of the first bubble, called bubble 1, from its initiation to its maximum volume. ρ is defined as R max2 /R max1 , where R max1 is the maximum radius of bubble 1, and R max2 is the maximum radius of the second bubble, called bubble 2. γ is defined as d/(R max1 +R max2 ), where d is the initial distance in between the bubble pair when they are just generated.…”
Section: Introductionmentioning
confidence: 99%